Cells with dendritic morphology and bright interleukin-1 alpha staining circulate in the blood of patients with rheumatoid arthritis. - Barkley, D; Feldmann, M; Maini, R (1990)
Freshly isolated peripheral blood mononuclear cells (PBMC) from 10 healthy volunteers, 28 patients with rheumatoid arthritis (RA), eight patients with osteoarthritis, and five patients with ankylosing spondylitis were examined for interleukin-1 alpha (IL-1 alpha) and interleukin-1 beta (IL-1 beta) production using monoclonal antibodies and an indirect immunofluorescent method. In freshly isolated PBMC from healthy controls very few cells were stained for either IL-1 type. All 20 RA patients who were not receiving parenteral gold therapy had PBMC staining for IL-1 alpha. In these patients, up to 7.5% of PBMC showed bright IL-1 alpha staining (range 1.2-7.5%). No IL-1 beta staining was seen. These IL-1 alpha-staining cells had a dendritic morphology and the percentage of cells staining correlated well with levels of C-reactive protein, an index of disease activity in these RA patients. Significantly fewer IL-1 alpha-staining cells were present in the peripheral blood of RA patients receiving gold therapy and in the blood of patients with osteoarthritis and ankylosing spondylitis. These IL-1 alpha-containing cells, circulating in the blood of RA patients and correlating with disease activity have not been previously described. These results support the idea that IL-1 alpha plays an important role in the pathogenesis of rheumatoid inflammation.